2020
DOI: 10.1039/c9nh00291j
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic nanoparticle technology for cardiovascular disease detection and treatment

Abstract: Biomimetic nanoparticle technology has the potential to significantly improve the clinical management of cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 226 publications
0
47
0
Order By: Relevance
“…Zhang et al recently reported neutrophil membrane-coated nanoparticles to alleviate inflammatory arthritis and platelet membrane-coated metal-organic framework nanoparticles to target gene silencing in vivo 22 , 23 . Most recently, cell membrane coating nanotechnology has been applied to treat certain cardiovascular diseases 24 . For instance, it has been reported that platelet membrane-coated NPs have been applied to detect and treat atherosclerosis 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al recently reported neutrophil membrane-coated nanoparticles to alleviate inflammatory arthritis and platelet membrane-coated metal-organic framework nanoparticles to target gene silencing in vivo 22 , 23 . Most recently, cell membrane coating nanotechnology has been applied to treat certain cardiovascular diseases 24 . For instance, it has been reported that platelet membrane-coated NPs have been applied to detect and treat atherosclerosis 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…The microencapsulation technique represents another potential strategy for a successful administration of IL-4/IL-13 [ 187 ]. A recent study demonstrated that IL-4/IL-13-encapsulated biodegradable microspheres displayed prolonged half-life and effectively suppressed inflammatory activity of osteoarthritic chondrocytes in in vitro assay [ 188 ].…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…However, triggers of atherosclerosis, which include hypertension, a diet high in saturated fats and obesity, initiate the expression of adhesion molecules that allow the entry of lipids into the vascular wall and the subsequent recruitment of leukocytes to the affected area (Rafieian-Kopaei et al, 2014). The use of cell membrane-based biomimetic NPs for these applications have focused on mimicking various cell membranes (e.g., as platelets and leukocytes) and protein complexes important for good cardiovascular health [i.e., high-density lipoprotein (HDL); Park et al, 2020].…”
Section: Cardiovascular Diseasementioning
confidence: 99%